Predictors of First-Pass Effect in Endovascular Thrombectomy With Stent-Retriever Devices for Acute Large Vessel Occlusion Stroke - Chen, Chu; Zhang, Tangqin; Xu, Youqing; Xu, Xiangjun; Xu, Junfeng; Yang, Ke; Yuan, Lili; Yang, Qian; Huang, Xianjun; Zhou, Zhiming (Frontiers in Neurology, 2022)
Background and Purpose Successful recanalization after the first pass of the device in endovascular thrombectomy (EVT) can significantly improve patients' prognosis. We aimed to investigate the possible factors that influence achieving the first-pass effect (FPE). Methods We retrospectively analyzed the patients who underwent EVT caused by anterior circulation large vessel occlusion stroke (ALVOS) in our center. The FPE was defined as a successful recanalization [modified Thrombolysis in Cerebral Infarction (mTICI) 2b/3 defined as modified FPE (mFPE); mTICI 3 as true FPE (tFPE)] after one pass of the device without rescue therapy. Univariate and multivariate regression analyses were used to explore the predictors of FPE and the relationship between FPE and prognosis. Results There were 278 patients (age, 69.3 ± 10.9 years, male, 51.1%) included, 30.2% of them achieved mFPE, while 21.2% achieved tFPE. We found the higher clot burden score (CBS), the truncal-type occlusion, and the favorable anatomy of both extracranial and intracranial segments of the internal carotid artery (ICA) were associated with achieving mFPE. The higher CBS and truncal-type occlusion were statistically significant predictors of tFPE. Moreover, FPE was significantly associated with improved clinical outcomes, regardless of mFPE and tFPE. Conclusions The CBS, tortuosity of ICA, and angiographic occlusion type were independent predictors of achieving FPE. The rate of improved clinical and safety outcomes was higher in patients with FPE, which has important clinical significance.